USE OF DIGITAL MARKETING MECHANISMS IN FARM DEVELOPMENT - Nazarova Gulruh Umarjonovna, (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2026)
This article analyzes the factors aimed at forming a marketing mechanism and increasing the competitiveness of farms in the agricultural sector. The study examines the main aspects of developing an effective marketing mechanism for farms, using digital technologies and innovative marketing tools, market segmentation, pricing policy, and branding. The study also covers practical methods and approaches necessary for the successful sale of farm products in the market and increasing their competitiveness, including issues of environmentally friendly products and quality improvement.